1996
DOI: 10.1002/eji.1830261257
|View full text |Cite
|
Sign up to set email alerts
|

The role of tyrosine phosphorylation and PTP‐1C in CTLA‐4 signal transduction

Abstract: Recently, there has been increasing interest in the inhibitory regulators of lymphocyte activation, and in particular, the role of CD28 homologue CTLA-4 in the regulation of T cell responses. Interaction of CTLA-4 with B7 ligands inhibits T cell responses, including T cell proliferation and interleukin-2 (IL-2) secretion. The mechanism(s) responsible for CTLA-4 signal transduction are unknown, but it has been suggested that tyrosine phosphorylation is involved. Here we demonstrate that phorbol ester phorbol 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…There is clear evidence for the role of tyrosine phosphatase activity in Ly49A-mediated inhibitory signals. Although SHP-2 and SHIP can bind to the Ly49A ITIM motifs, SHP-1 appears to be the primary phosphatase required for signal transduction (for a review, see Lanier 43 ). Inhibitory NKR engagement prevents early protein tyrosine kinase (PTK)-dependent activation signals in NK cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is clear evidence for the role of tyrosine phosphatase activity in Ly49A-mediated inhibitory signals. Although SHP-2 and SHIP can bind to the Ly49A ITIM motifs, SHP-1 appears to be the primary phosphatase required for signal transduction (for a review, see Lanier 43 ). Inhibitory NKR engagement prevents early protein tyrosine kinase (PTK)-dependent activation signals in NK cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that normal levels of SHP-1 are not required for CTLA-4-mediated T-cell inhibition. 43 Some evidence for a role for tyrosine phosphatase SHP-2 has been reported. Demonstration that catalytically active SHP-2 binds to the cytoplasmic tail of CTLA-4 25,44 suggests that this tyrosine phosphatase is relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In this figure, the absolute percentage of positive cells in the spleen (above the bars and underlined in the figure) was determined by multiplying the percentage of positive cells within the gate by the percentage of total splenocytes within the gate. The absolute numbers of cells (ϫ10 3 ) of the particular phenotype observed in the spleen are given by the numbers directly above the bars. These were determined by multiplying the absolute percentage of positive cells by the total cell number.…”
Section: The Phenotype Of Spleen Cells In Tumor-bearing Mice Is Altermentioning
confidence: 99%
“…The development of metastatic disease suggests that this defense sometimes fails, a hypothesis supported by the results demonstrating reduced functional ability by T cells from tumor-bearing hosts. Some of the possible underlying mechanisms to explain this phenomenon include ineffective signal transduction following ligation of the TCR (1, 2), the preferential secretion of Th2 cytokines favoring the development of Ab-mediated responses at the expense of those that are cell mediated (3), and poor Ag-presenting ability of macrophages in the tumor-bearing host (4). Previously, we reported that although mice initially developed an immune response against CMS5 tumor cells, it waned with time (5).…”
mentioning
confidence: 99%
“…We previously reported that CTLA-4-mediated inhibition could be reversed by phorbol ester, suggesting that the regulation of tyrosine phosphorylation might be involved in the process (33). However, the CTLA-4 inhibitory pathway seems to be intact in motheaten viable mice, indicating that normal levels of the tyrosine phosphatase SHP are not essential for CTLA-4 function (33). Other studies showed that several tyrosine kinases and kinase substrates are hyperphosphorylated in CTLA-4 Ϫ/Ϫ mice (19).…”
mentioning
confidence: 99%